DEVELOPMENT OF EDUCATIONAL RESOURCES BY USE OF WEBBASED APPLICATION TRELLO - Valery G. Zaitsev; Anastasia A. Zheltova; Elena V. Tibir’kova (Высшее образование в России, 2016)
Abstract. This paper highlights the features of web-based project management system Trello that could be used to develop various tools for educational web-sites. The authors show some practical examples of Trello use for learning and self-learning. The elements of Trello’s boards can be easily combined to form highly flexible educational workflow.